Raman Micro-Spectroscopic Analysis of Cultured HCT116 Colon Cancer Cells in The Presence of Roscovitine - Özel, Ayşen; Balcı, Kubilay; Çoker, Ajda; Palavan-Ünsal, Narçin; Özalpan, Atilla; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL; ARISAN, ELİF DAMLA (Pergamon-Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, England, 2011)
Raman micro-spectroscopic analysis of cultured HCT116 colon cancer cells in the presence of roscovitine, [seliciclib, 2-(1-ethyl-2-hydroxy-ethylamino)-6-benzylamino-9-isopropylpurine], a promising drug candidate in cancer therapy, has been performed for the first time. The aim of this study was to investigate modulations in colon cancer cells induced by roscovitine. Raman spectra of the cultured HCT116 colon cancer cells treated with roscovitine at different concentrations (0,5,10, 25 and 50 mu M) were recorded in the range 400-1850 cm(-1). It was shown that the second derivative profile of the experimental spectrum gives valuable information about the wavenumbers and band widths of the vibrational modes of cell components, and it eliminates the appearance of false peaks arising from incorrect baseline corrections. In samples containing roscovitine, significant spectral changes were observed in the intensities of characteristic protein and DNA bands, which indicate roscovitine-induced apoptosis. Roscovitine-induced apoptosis was also assessed by flow cytometry analysis, and analysis of propidium iodide staining. We observed some modifications in amide I and III bands, which arise from alterations in the secondary structure of cell proteins caused by the presence of roscovitine. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: colon cancer; cultured cells; raman micro-spectroscopy; roscovitine; seliciclib; living cells; apoptosis; death; model; kolon kanseri; kültürlenmiş hücreler; roskovitin; yaşayan hücreler; apoptoz; ölüm